Unveiling the Impact of Online Events on Brand Image: A Quantitative Approach - Kurnia khafidhatur rafiah; Muhammad Rifki Aliyasin (PT. Intelek Cendikiawan Nusantara, 2024)
In the past two years, the world of marketing communication has undergone significant changes due to the global Covid-19 pandemic. One strategy that has been widely used is online or virtual events, which have become an effective way to conduct marketing during the pandemic. These virtual events aim to promote companies or brands by hosting online events that engage consumers. PT ABC, a startup in the edutech sector, has utilized online events as a marketing medium with the goal of enhancing their brand image, making it more recognized as a brand with a good reputation among the public, particularly among students. This study aims to determine the impact of online events on ABC’s brand image, as well as the effects of organizing such events. The method used is a quantitative approach, collecting data through questionnaires distributed to 99 respondents who participated in ABC’s online events, consisting of high school students, university students, and fresh graduates. The results of the study indicate that online events have a significant impact on ABC's brand image. Additionally, there is a moderate relationship between online events and brand image, with an influence of 32%. Online events have also positively impacted the increase in ABC's website traffic.